Beyond Traditional Therapy: Loose Parts as an Innovative Solution for Children's Speech Development - Zuhraini, Asri; Chamidah, Atien Nur (Journal of Innovation and Research in Primary Education, 2025)
Speech delays affect 5-10% of preschool children, requiring effective intervention strategies that can be implemented within regular educational settings. Loose parts materials, consisting of open-ended objects without predetermined functions, offer potential for addressing communication challenges through multimodal learning experiences. This study investigated the effectiveness of loose parts media in enhancing speech development among early childhood children experiencing delays. A classroom action research design following the Kemmis and McTaggart model was implemented across two intervention cycles at TK Negeri 2 Muara Ancalong, Indonesia. Four children aged 5-6 years with identified speech delays participated in structured activities using various loose parts materials including natural objects (seeds, stones) and manufactured items (bottle caps, wooden pieces). Speech development was assessed using six indicators: object naming ability, simple question answering, desire expression, basic storytelling, vocabulary expansion, and articulation clarity. Data were collected through systematic observation and analyzed using descriptive statistics. All participants demonstrated measurable improvement in speech development indicators. Three children advanced one developmental category from baseline to post-intervention assessment, while one participant achieved exceptional progress of two categories. Pre-intervention mean scores of 1.6 increased to 2.8 following the intervention. Qualitative observations revealed enhanced communication confidence, increased vocabulary usage, and improved social interaction patterns during loose parts activities. Loose parts media represents an effective, accessible intervention strategy for addressing speech delays in early childhood settings. The approach's integration of tactile manipulation, visual discrimination, and verbal expression within meaningful play contexts facilitates natural language development while promoting collaborative competencies. The intervention's cost-effectiveness and classroom compatibility support its implementation as a viable alternative to traditional speech therapy approaches, though individual variation in response patterns indicates the need for differentiated intervention strategies.